Menyikapi “Penyedia Jasa Keuangan Baru” Dengan Platform Digital Yang Dimanfaatkan Pelaku Kejahatan Sebagai Sarana Tindak Pindana Pencucian Uang Dan Pendanaan Terorisme - Arief Wind Kuncahyo (Jurnal Fundamental Justice, 2021)
ABSTRACT As a Supervisory and Regulatory Institution, The Financial Services Authority (OJK) has a very important role in the Anti Money Laundering and Combating Financing Terorisme (AML CFT) regime. In the Anti Money Laundering Law, OJK is given the authority to regulate the principles of recognizing Service Users and supervising the compliance of Reporting Parties in implementing the Principles of Recognizing Service Users. With current technological developments, challenges arise related to the implementation of the AML-CFT program, especially by “new Financial Service Providers” who are not included as Reporting Parties in the Anti Money Laundering Law but have the potential to be exploited by criminals to commit crimes of money laundering and terrorism financing. This research will examine the presence of new financial service providers in relation to the implementation of the AML-CFT program. Keyword: Money Laundering, Combating Terrorism, Financial Services Provider, Financial Technology.